Pengaruh Sistem Pembayaran COD, Online Customer Review, Online Customer Rating, Dan Diskon Terhadap Keputusan Pembelian Di E-Commerce Shopee - Bahari, Romi Chandra; Arifin, Rois; Ramadhan, Tri Sugiarti (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract Advances in technology and information have shifted people's shopping behavior, for example on Shopee, which has the highest number of users in Indonesia. The high number of users and competition have had an impact on Shopee, such as product mismatch. Previous studies have shown various findings regarding COD, online customer reviews, online customer ratings, and discounts on purchasing decisions. No previous study has investigated these four variables simultaneously. This study examines the impact of COD, online customer reviews, online customer ratings, and discounts on purchasing decisions on Shopee. The findings are expected to support e-commerce companies in creating more efficient marketing approaches. This is a quantitative study using explanatory research techniques to test the causal relationships between variables, with a sample of 110 Shopee users in Malang City selected through snowball sampling. Data analysis was conducted using multiple linear regression analysis with SPSS. The findings revealed that Cash On Delivery, Online Customer Rating, and Discounts partially showed a significant influence on purchasing decisions on Shopee, while Online Customer Reviews did not show a significant impact. Simultaneously, all four variables significantly influence purchasing decisions on Shopee in Malang City. These results indicate that COD, online customer reviews, online customer ratings, and discounts are the primary factors for consumers when making online transactions. Keywords: Cash On Delivery (COD), Online Reviews, Online Ratings, Discounts, Purchasing Decision, Shopee, Malang City